Prognostic Value of the LATITUDE and CHAARTED Risk Criteria for Predicting the Survival of Men with Bone Metastatic Hormone-Naïve Prostate Cancer Treated with Combined Androgen Blockade Therapy: Real-World Data from a Japanese Multi-Institutional Study. (2nd July 2020) - Kawahara, Takashi; Yoneyama, Shuko; Ohno, Yoshio; Iizuka, Junpei; Hashimoto, Yasunobu; Tsumura, Hideyasu; Tabata, Ken-ichi; Nakagami, Yoshihiro; Tanabe, Kazunari; Iwamura, Masatsugu; Uemura, Hiroji; Miyoshi, Yasuhide
Abstract : Background . The CHAARTED and LATITUDE trials demonstrated a prolonged overall survival (OS) for metastatic hormone-naïve prostate cancer (mHNPC) patients who receive up-front docetaxel or abiraterone acetate. These studies used their own risk criteria: CHAARTED trial defines high- and low-volume diseases and LATITUDE trial targeting a high-risk disease. The present study explored whether or not the CHAARTED and LATITUDE criteria were useful for predicting the outcome in Japanese bone mHNPC patients, including elderly patients (≥70 years). Methods . A total of 532 mHNPC patients diagnosed from 2004 to 2014 in multithird referral cancer centers were enrolled in this study. All patients had bone metastasis and received combined androgen blockade treatment as an initial hormonal therapy. Results . The number of patients with CHAARTED low-volume and high-volume diseases was 178 (33.5%) and 354 (66.5%), respectively. On the contrary, the number of patients with LATITUDE low-risk and high-risk diseases was 157 (29.5%) and 375 (70.5%), respectively. A total of 307 (57.7%) patients were defined as having both CHAARTED high-volume and LATITUDE high-risk disease. The median castration-resistant prostate cancer- (CRPC-) free survival was 12.5 months for the CHAARTED high volume, 56.9 months for the CHAARTED low volume, 13.6 months for the LATITUDE high risk, and 37.3 months for the LATITUDE low risk, respectively. The OS was 50.1 months in patients with CHAARTED high-volume disease, 95.1 months in patients with CHAARTED low-volume disease, 54.0 months in patients with LATITUDE high-risk disease, and 92.7 months in patients with LATITUDE low-risk disease, respectively. This trend was also observed in elderly (≥70 years old) patients. Conclusions . The patients with CHAARTED high-volume disease or LATITUDE high-risk disease showed a shorter CRPC-free survival and a shorter OS than those in the CHAARTED low-volume disease group or in the LATITUDE low-risk group among Asian Japanese bone metastatic HNPC patients.